Survey of the Hymenoptera Fauna in a "Caatinga" Area in the State of Rio Grande do Norte, Northeastern Brazil - Fernandes, Daniell Rodrigo Rodrigues (2014)
The aim of this study was to carry out a survey of the fauna of the Hymenoptera families in an area of Caatinga in Mossoró, state of Rio Grande do Norte, Brazil. The samplings were carried out with Malaise traps, active between 6th of February and 6th of March, 2007 and between 13th March and 14th April, 2008. A total of 5,057 Hymenoptera, belonging to 12 superfamilies and 36 families, were collected. The most abundant superfamilies were: Chalcidoidea (1,206 specimens/23.85% of the total), Vespoidea (886/17.52%), Ichneumonoidea (837/16.55%) and Platygastroidea (801/15.84%) and the most abundant families were: Platygastridae (801/15.84%), Braconidae (616/12.18%), Pteromalidae (583/11.53%), Figitidae (454/8.98%), Pompilidae (444/8.78%) and Formicidae (268/5.30%). The data obtained allow us to affirm that the Caatinga encompasses substantial family richness of Hymenoptera and that renewed effort is necessary to sample its fauna in a more extensive way. Levantamento da Fauna de Hymenoptera em uma Área de Caatinga do Estado do Rio Grande do Norte, Nordeste do Brasil Resumo. O objetivo deste estudo foi realizar levantamento das famílias de himenópteros presentes em área de Caatinga em Mossoró, Estado do Rio Grande do Norte, Brasil. As amostragens foram realizadas com armadilhas Malaise, entre 6 de fevereiro e 6 de março de 2007 e 13 de março e 14 de abril de 2008. Foram coletados 5.057 himenópteros pertencentes a 12 superfamílias e 36 famílias. As superfamílias mais abundantes foram: Chalcidoidea (1.206 exemplares/23,85% do total), Vespoidea (886/17,52%), Ichneumonoidea (837/16,55%) e Platygastroidea (801/15,84%) e as famílias mais abundantes foram: Platygastridae (801/15,84%), Braconidae (616/12,18%), Pteromalidae (583/11,53%), Figitidae (454/8,98%), Pompilidae (444/8,78%) e Formicidae (268/5,30%). Os dados obtidos demonstram grande riqueza de famílias de himenópteros na Caatinga e que estudos adicionais são necessários para estabelecer a riqueza desta fauna de forma mais extensiva.